Developing Critical Thinking Skills in Secondary School Students: The Potential for Strategic Management through Problem-Posing Instructional Strategy (International Journal of Academic Research in Progressive Education and Development, 2022)
Critical thinking is one of the essential skills in learning. Malaysia has continuously made an effort to embed critical thinking in the curriculum of secondary school because many subjects in the secondary schools levels involve a vast amount of critical thinking elements. One of the distinguished elements that needed to be enhanced to promote critical thinking is the questioning skills. Currently, many students do not ask appropriate questions during their lessons especially in-depth questions that require critical thinking skills. This is a call to introduce an instructional strategy in the classroom to help students to ask the right questions confidently and at the same time encourage them to be further involved in the active discussion in the class. Problem-posing instructional strategy (PPIS) is one of the strategies used to promote critical thinking among students. This paper will review previously conducted studies to identify activities and approaches used in PPIS and systematically arrange them in order to be used as a strategic management tool to develop critical thinking among students. The purpose of this study is to address the potential of problem-posing instructional strategy (PPIS) as a strategy to develop critical thinking for secondary school students. The key research questions of this study were 1. What are the activities of PPIS commonly used in previous studies? 2. How can PPIS activities be arranged systematically to construct a PPIS model to develop critical thinking? The findings show the activities and approaches employed by previous studies can be arranged in a systematic sequence to construct a model for PPIS. The findings provide teachers with a model to implement PPIS as well as the processes involved in PPIS to promote critical thinking in the classroom.
Keywords: Problem-Posing, Critical Thinking, Problem-Posing Instructional Strategy, Higher Order Thinking Skills, 21st Century Pedagogy.